2008
DOI: 10.1038/jp.2008.119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters do not adequately predict outcome in necrotizing enterocolitis: a multi-institutional study

Abstract: Objective: Necrotizing enterocolitis (NEC) remains a major cause of neonatal morbidity and mortality. Some infants recover uneventfully with medical therapy whereas others develop severe disease (that is, NEC requiring surgery or resulting in death). Repeated attempts to identify clinical parameters that would reliably identify infants with NEC most likely to progress to severe disease have been unsuccessful. We hypothesized that comprehensive prospective data collection at multiple centers would allow us to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 34 publications
2
72
0
2
Order By: Relevance
“…However, the surgery can cause short bowel syndrome and inadequate absorption of nutrients. Thus, better therapeutic measures are needed (6,7). Studies have indicated that the scores for neonatal acute physiology-perinatal extension-II and metabolic derangement acuity were insufficient measures for deciding on surgical treatment for the patients affected by NEC (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the surgery can cause short bowel syndrome and inadequate absorption of nutrients. Thus, better therapeutic measures are needed (6,7). Studies have indicated that the scores for neonatal acute physiology-perinatal extension-II and metabolic derangement acuity were insufficient measures for deciding on surgical treatment for the patients affected by NEC (8).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Moss et al 17 attempted to delineate clinical predictors of NEC in a multi-institutional study. A total of 455 infants were evaluated prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Various studies have been undertaken to elucidate risk factors for the development of NEC. [14][15][16][17][18] The two most commonly observed risk factors appear to be prematurity and enteral feeding. The use of breast milk may be a protective factor.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact etiology of necrotizing enterocolitis (NEC) remains unknown, researchers suggest that it is multifactorial. Prematurity (with an immature GIT and immature host defenses) is the primary risk factor [3]; ischemia and/or reperfusion injury, exacerbated by the activation of proinflammatory intracellular cascades, may play a significant role [4]. Neonatal sepsis is considered a risk factor for NEC [5].…”
Section: Introductionmentioning
confidence: 99%